MODEL MANAJEMEN MUTU PELAYANAN ANTENATAL CARE DI FASILITAS KESEHATAN PRIMER - Meyana Marbun; Keysha Iszmi Erhan; Amanda Sahfitri (Jurnal Minfo Polgan, 2022)
In primary healthcare facilities, quality management of ANC services is crucial to ensure that every pregnant woman receives comprehensive, standardized care. This literature review aims to identify, analyze, and synthesize various quality management models that have been implemented or proposed for ANC services in primary healthcare facilities. The review indicates that existing models often incorporate a systems approach, continuous improvement cycles, and multidisciplinary participation. Key challenges include resource availability, health worker capacity, and adherence to standards. An ideal model should consider the local context, be patient-centered, and supported by a robust monitoring and evaluation system.